Prognostic Significance of Cyclins A2, B1, D1, and E1 and CCND1 Numerical Aberrations in Oral Squamous Cell Carcinomas - Luís Silva Monteiro; Márcio Diniz-Freitas; Saman Warnakulasuriya; Tomás Garcia-Caballero; Jerónimo Forteza-Vila; Máximo Fraga (Analytical Cellular Pathology, 2018)
We analysed the expression of cyclins A2, B1, D1, and E1 by immunohistochemistry and numerical aberrations in CCND1 gene by fluorescence in situ hybridization technique in 67 primary oral squamous cell carcinomas (OSCC). Cyclin A2 expression was observed in 54 (83.1%) tumours, cyclin D1 in 58 (89.2%), cyclin B1 in 39 (60%), and cyclin E in 21 (32.8%). CCND1 region analysis revealed 26 (43.3%) tumours with the presence of numerical aberrations which were correlated with cyclin D1 high expression (Rho = 0.48; p<0.001). Twenty-nine (45.3%) tumours were classified as high proliferative tumours assessed by Ki-67 protein expression and correlated with tumours with high expression of cyclin A2 (Rho = 0.30; p=0.016) and cyclin B1 (Rho = 0.37; p=0.003). In multivariate analysis for an overall five-year survival (OS), we found an adverse independent prognostic value for cyclin A2 high expression (p=0.031) and for advanced tumour stage (p<0.001). Our results confirm that several cyclins are commonly expressed in OSCC. CCND1 gene is abnormal in more than one-third of the cases and is frequently associated with cyclin D1 high expression. Moreover, cyclin A2 high expression is an independent indicator of worse OS suggesting that this protein may serve as a reliable biological marker to identify high-risk subgroups with poor prognosis.